2009
DOI: 10.1097/brs.0b013e3181ab64e9
|View full text |Cite
|
Sign up to set email alerts
|

Spine Deformities in Rare Congenital Syndromes

Abstract: For optimal patient care, it is necessary to have a clear understanding of exotic congenital syndromes and how they may impact on both the presentation of spinal deformity and the response to treatment, as well as how they may introduce additional morbidity into standard treatment plans. It is clear that with this understanding that preoperative strategies can be employed to enhance the safety of spinal treatment for these unique children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 61 publications
0
77
0
7
Order By: Relevance
“…Les autres doigts sont fléchis au niveau de l'articulation interphalangienne proximale. La fréquence d'une déformation de la colonne vertébrale est très variable (entre 2,5 % et 65,9 %) [10]. Les plis de flexion articulaire sont souvent absents et il peut exister des fossettes à proximité des articulations.…”
Section: Discussionunclassified
“…Les autres doigts sont fléchis au niveau de l'articulation interphalangienne proximale. La fréquence d'une déformation de la colonne vertébrale est très variable (entre 2,5 % et 65,9 %) [10]. Les plis de flexion articulaire sont souvent absents et il peut exister des fossettes à proximité des articulations.…”
Section: Discussionunclassified
“…According to previous work, malformations of the ribs, chest cavity, and scapulae are often a common finding with severe scoliosis [1, 2,8,10]. Additionally, it has been suggested that when spinal deformities are severe, thoracic insufficiency syndrome is often present as the thorax is unable to support normal respiratory movements [6].…”
Section: Discussionmentioning
confidence: 99%
“…They described 2 patients with short neck and short thorax resulting from multiple congenital vertebral and rib cage malformations [8,9]. In 1978, Solomon et al [4] classified cases of JLS into two phenotypic groups: STD and SCD.…”
Section: Discussionmentioning
confidence: 99%